Biological characterization of mulberry leaves bioconverted with Viscozyme L - Kim, Young Wook; Yu, Sun Nyoung; Kim, Kwang Youn; Kim, Sang Hun; Park, Bo Bae; Oh, Hyun Cheol; Kim, Dong Seob; Park, Kwang Il; Ahn, Soon Cheol (Molecular & cellular toxicology, 2023)
Background Mulberry ( Morus alba L.) leaves is a Korean medicinal herb that shows bioactive compounds such as quercetin, anthocyanins and polysaccharides. Bioconversion with Viscozyme L process could be producing enriched physiologically active compounds of mulberry leaves. Objective Thus, this study focused on the purification of the bioconverted compounds responsible for ethyl acetate extraction and column chromatography using normal-phase silica gel and Sephadex LH-20. Results In this study, we obtained the purified compounds, MAV 1, MAV 2 and MAV 3, which were identified as caffeic acid, quercetin, and kaempferol, by analysis of nuclear magnetic resonance spectroscopy. Also, we optimized the yield of the most active compound, quercetin in 20% substrate, 5% enzyme, at 37 °C and pH 4 for 24 h, 2.34 ± 0.03 mg of quercetin was produced from 1 g of dried mulberry leaves. Furthermore, we showed that bioconverted compounds have biological activities such as α-glucosidase, acetylcholinesterase inhibitory, cytotoxicity activity, tyrosinase, xanthine oxidase (XO) and pancreatic lipase inhibition. Conclusion These results indicate that the enhanced activities of α-glucosidase, tyrosinase, xanthine oxidase inhibitory activities, and the anti-oxidant properties bioconverted from mulberry leaves with Viscozyme L. One of them, the quercetin which is a potent α-glucosidase inhibitor bioconverted from mulberry leaves with Viscozyme L has an anti-diabetic effect. And it can be used for the development of health foods and pharmaceutical products.